Simulation Evaluation of Vehicle Movement Model Using Spatio-Temporal Grid Reservation for Automated Valet Parking - Kotaro Yamamoto; Rui Teng; Kenya Sato (IEEE Open Journal of Intelligent Transportation Systems)
Automated valet parking (AVP) systems aim to use automated driving technology to park a vehicle from the passenger’s boarding/exiting location to a parking space in a parking lot and recall the vehicle from the parking space to the boarding/exiting location. For multiple vehicles to move efficiently through a parking lot, travel must be mediated between each vehicle. We have proposed a driving control method that improves the efficiency of AVP by using the Spatio-Temporal Grid Reservation mechanism. We previously compared it with an autonomous driving, which showed that the proposed method improved the efficiency of vehicle movement when vehicles are entering small parking lots. In this paper, we modified our previous method to accommodate the increasing number of vehicles in a parking lot and created Spatio-Temporal Grid Model as a vehicle movement model. we evaluate this model by comparing it with Conflict Zone Model and MAPF Model created by the methods proposed in related studies, in addition to an autonomous driving model. We performed simulations varying the percentage of vehicles arriving at the parking lot and showed that Spatio-Temporal grid model improves the efficiency of vehicle movement when vehicles are entering and exiting the lot.